Characterisation of arsenic contamination in groundwater by statistical methods - Anwar, Faisal; Kawonine, N. (Inderscience Publishers, 2012)
Statistical investigation on groundwater arsenic concentration data of southwest Bangladesh was performed. Two data sets of 1998-99 and 2002-03 were selected for this analysis. Summary statistics of the data shows that the mean concentration exceeds the Bangladesh limit (0.05mg/l) in all areas. Normality of arsenic concentration data was checked by frequency histogram, skewness coefficient and chi-square goodness-of-fit test and found that the arsenic contamination is not normally distributed. The data were checked for spatial distribution by plotting contour maps and it shows substantial spatial variation. Temporal variability was tested by students t-test and found that the area closer to the confluence of Ganges-Meghna-Jamuna river showing significant temporal variation. Vertical variability of arsenic contamination shows that more than 80-90% of the shallow aquifer (<150m) are contaminated with arsenic (>0.05mg/l). Though deep aquifer (>150m) is still considered as arsenic free but 1-3% of deep tubewells water was also found contaminated with arsenic.